Inclusive and Collaborative Leadership in Decision Making - Jeremy Kautza (Academic Chairpersons Conference Proceedings, 2018)
Based on the best-selling book, "Getting to Yes" by Fisher, Ury, and Patton (3rd Edition, 2011), Madison College has adopted an interest-based approach for making college-wide decisions as well as for resolving issues in programs and departments. In this session you'll experience the elements of an interest-based approach to problem solving that you can use in addressing conflicts in any work situation. (It works at home too!) You'll leave with a new-found appreciation for the process--its ease and effectiveness--along with materials you can take back to your college to spark your transformation.
Keywords: Collaborative Negotiation Inclusive Decision Transparent Win Leadership Conflict Resolution Problem Solving